CX3CL1 and IL-15 Promote CD8 T cell chemoattraction in HIV and in atherosclerosis. - Soumya Panigrahi; Bonnie Chen; Mike Fang; Daria Potashnikova; Alexey A Komissarov; Anna Lebedeva; Gillian M Michaelson; Jonathan M Wyrick; Stephen R Morris; Scott F Sieg; Mirko Paiardini; Francois J Villinger; et al. (PLoS Pathogens, 2020)
Atherosclerotic cardiovascular disease (ASCVD) remains an important cause of morbidity in the general population and risk for ASCVD is increased approximately 2-fold in persons living with HIV infection (PLWH). This risk is linked to elevated CD8 T cell counts that are abundant in atherosclerotic plaques and have been implicated in disease pathogenesis yet the mechanisms driving T cell recruitment to and activation within plaques are poorly defined. Here we investigated the role of CD8 T cells in atherosclerosis in a non-human primate model of HIV infection and in the HIV-uninfected elderly; we sought to identify factors that promote the activation, function, and recruitment to endothelium of CX3CR1+ CD8 T cells. We measured elevated expression of CX3CL1 and IL-15, and increased CD8 T cell numbers in the aortas of rhesus macaques infected with SIV or SHIV, and demonstrated similar findings in atherosclerotic vessels of HIV-uninfected humans. We found that recombinant TNF enhanced the production and release of CX3CL1 and bioactive IL-15 from aortic endothelial cells, but not from aortic smooth muscle cells. IL-15 in turn promoted CX3CR1 surface expression on and TNF synthesis by CD8 T cells, and IL-15-treated CD8 T cells exhibited enhanced CX3CL1-dependent chemoattraction toward endothelial cells in vitro. Finally, we show that CD8 T cells in human atherosclerotic plaques have an activated, resident phenotype consistent with in vivo IL-15 and CX3CL1 exposure. In this report, we define a novel model of CD8 T cell involvement in atherosclerosis whereby CX3CL1 and IL-15 operate in tandem within the vascular endothelium to promote infiltration by activated CX3CR1+ memory CD8 T cells that drive further endothelial activation via TNF. We propose that these interactions are prevalent in aging and in PLWH, populations where circulating activated CX3CR1+ CD8 T cell numbers are often expanded.